Humanistic care provision beyond duty as a new approach to holistic care: a qualitative study - Sima Babaei; Somayeh Haghighat; Narges Kheirollahi (Shahrekord University of Medical Sciences, 2022)
Background and aims: Patients in intensive care unit (ICU) experience not only serious physical problems, but also emotional, psychological, financial, and social problems. Therefore, they need holistic care (HC). The aim of this study was to explore nurses' beliefs about HC provision to patients in ICU. Methods: This qualitative study was conducted in 2019-2020 using the content analysis approach. Participants were sixteen nurses purposively selected from four ICUs of two hospitals affiliated to Isfahan University of Medical Sciences, Isfahan, Iran. Data were collected using face-to-face in-depth semi-structured interviews and analyzed through conventional content analysis. The COREQ checklist was used as a guideline to report the findings. Results: A total of 304 primary codes were generated during data analysis which were grouped into twelve subcategories and two main categories. The two main categories of the study were purposeful nursing care and humanistic care provision beyond duty. Conclusion: Nurses attempt to provide HC and go beyond their assigned duties in HC provision.